The Effects of Lung Ischaemia/Reperfusion on TRPM Gene Expression - Atabay, H. D.; Demir, T.; Dokuyucu, R.; Yumrutas, O.; Oztuzcu, S.; Ceribasi, A. O.; Bagci, C. (Univ West Indies Faculty Medical Sciences, 2021)
Objective: Transient receptor potential melastatin (TRPM) are integral membrane proteins that have broad range of cellular functions. Roles of TRPM2, TRPM3, TRPM4 and TRPM7 among these channels are very important, and their roles in lung ischaemia/reperfusion injury have not been evaluated yet. The aim of this study is to investigate the contribution of these genes in lung ischaemia/reperfusion injury and evaluate histopathology of tissues. Methods: A total of 40 Wistar albino rats were enrolled for the study. Ischaemia was performed by the application of an atramvatic clamp to pulmonary artery. Gene expressions were determined by the semi-quantitative reverse transcription-polymerase chain reaction method. Histopatholical evaluations were held by a standard haematoxyline-eosin staining. Results: The major histopathological tissue damage was observed in ischaemia performed groups, and expression of TRPM channels was found to be obviously downregulated. Substantial changes were determined between TRPM2, TRPM3, TRPM4 and TRPM7 and lung ischaemia/reperfusion injury. In particular; expression of TRPM2 and TRPM7 was reversibly downregulated in ischaemia. Yet, the expression of TRPM3 and TRPM4 was irreversibly downregulated after ischaemia. Conclusion: Consequently, these results indicate that TRPM family of cation channels may have significant roles in the lung ischaemia/reperfusion injury.
Keywords: Lung ischaemia reperfusion; transient receptor potential channels; TRPM2/3/4/7